Marcello Piacentini: A case of controversial heritage - Malone, Hannah (My University, 2018)
As the most prominent architect and urban designer of Italy’s fascist regime, Marcello Piacentini (1881–1960) left an indelible mark on numerous cities across Italy. Nonetheless, his reception has been marred by controversy. Whereas some accounts dismiss Piacentini’s career as unredeemably tainted by associations with fascism, others acknowledge his skill, professionalism and inventiveness. Efforts to deal with the history of Piacentini’s work have prompted a range of different approaches. Some scholars have attempted to disassociate morality and aesthetics by focusing exclusively on the formal characteristics of Piacentini’s urban and architectural projects. Others have addressed the historical context in which those projects were produced, and have viewed them as vehicles of fascist propaganda. In effect, Piacentini’s legacy invites questions of how buildings that were created under the aegis of Mussolini’s dictatorship carried political meanings, and whether those meanings remain current today. Those questions are investigated with respect to Piacentini’s Arch of Victory, built in Genoa in the 1930s. More broadly, they provide insights into the ways in which the fascist past has been handled and remains relevant today.
Architecture as Propaganda in Twentieth-Century Totalitarian Regimes. History and Heritage
PUBLISHED